Peculiarities Of Legal Bases of State Civil Service (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
the article considers the legal foundations of state civil service, its features, the organization of state civil service, including the legal status of state civil servants, the most important issue, which should be regulated by the relevant normative legal acts, in the scientific observation of the problematic sides of this issue, that is, various issues related to labor legislation, as well as opinions and views on its improvement, have been analyzed by the author from the scientific-theoretical point of view.